Effectiveness of Meme-Infused Didactics and Its Relationship in Improving Memory Retention of Grade 8 Chemistry Students Towards Learning Guide Development - Destajo, Evan Dwigth (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effectiveness of meme-infused didactics in enhancing the memory retention of Grade 8 chemistry students at Sto. Tomas City National High School during Academic Year 2025–2026. Anchored on Dual Coding Theory and Cognitive Load Theory, the study employed a descriptive-correlational research design involving 79 Grade 8 chemistry students selected through purposive sampling. Researcher-made pretest and posttest instruments and questionnaires, supported by adapted references and validated by experts, were used to measure academic performance, perceived effectiveness in terms of engagement, motivation, and learning enjoyment, and memory retention in terms of understanding of concepts, application of knowledge, and connecting concepts. Results showed that students’ academic performance substantially improved after exposure to meme-infused didactics, with 68.4% reaching the Mastered level in the posttest and 81.1% reaching performance levels aligned with or approaching mastery. Meme-infused didactics was rated Very Effective overall, particularly in engagement, learning enjoyment, and motivation. Its influence on memory retention was Highly Influential overall, especially in application of knowledge and connecting concepts, while understanding of concepts was Moderately Influential. Statistical results confirmed a significant difference between pretest and posttest performance and significant relationships between perceived effectiveness and memory retention. The study concluded that meme-infused didactics can support chemistry learning by improving engagement, motivation, enjoyment, academic performance, and retention. It recommends the institutional use of a Meme-Infused Didactics learning guide, supported by accurate, culturally relevant, and evidence-based instructional design. The study aligns with SDG 4, Quality Education, by supporting improved science instruction and learning recovery, and SDG 9, Industry, Innovation and Infrastructure, through educational innovation using digital culture. Its sustainability impact lies in promoting a low-cost, learner-centered, and institutionally adaptable strategy for improving chemistry instruction and memory retention.